PERAN INOVASI TEKNOLOGI DALAM GREEN TRANSPORTASI : MEWUJUDKAN GREEN ECONOMY DAN PEMBANGUNAN BERKELANJUTAN - Saniyyah, Reidah Daffa (Jurnal Ekonomi : Journal of Economic, 2024)
Issues related to the green economy have attracted the attention of experts in the field of development economics. However, research on the green economy is rarely linked to technological innovation in green transportation. Therefore, this research focuses on examining the role of green transportation in realizing green economy and development, as well as the impacts, challenges and strategies for electric vehicles. The research method used is a qualitative literature review method. The results of this research show that green electric vehicle transportation plays a role in realizing a green economy and sustainable development. Electric vehicles both in terms of economy and environment also have positive and negative impacts. The positive impacts include improved air quality, reduced dependence on fossil fuels, reduced financial burden on the owner, and energy efficiency. However, electric vehicles also have several challenges including the production of batteries that are not free from environmental impacts, limited mileage, lack of available charging infrastructure, very high taxes, and government transition in 2024. To overcome these challenges, there are several strategies that can be carried out including the implementation of tax incentives, establishing effective collaborations, conducting extensive public campaigns and developing charging infrastructure.